Turnover of sex chromosomes and speciation in fishes - Kitano, Jun (Environ Biol Fishes, 2011)
Closely related species of fishes often have different sex chromosome systems. Such rapid turnover of sex chromosomes can occur by several mechanisms, including fusions between an existing sex chromosome and an autosome. These fusions can result in a multiple sex chromosome system, where a species has both an ancestral and a neo-sex chromosome. Although this type of multiple sex chromosome system has been found in many fishes, little is known about the mechanisms that select for the formation of neo-sex chromosomes, or the role of neo-sex chromosomes in phenotypic evolution and speciation. The identification of closely related, sympatric species pairs in which one species has a multiple sex chromosome system and the other has a simple sex chromosome system provides an opportunity to study sex chromosome turnover. Recently, we found that a population of threespine stickleback (Gasterosteus aculeatus) from Japan has an X(1)X(2)Y multiple sex chromosome system resulting from a fusion between the ancestral Y chromosome and an autosome, while a sympatric threespine stickleback population has a simple XY sex chromosome system. Furthermore, we demonstrated that the neo-X chromosome (X (2)) plays an important role in phenotypic divergence and reproductive isolation between these sympatric stickleback species pairs. Here, we review multiple sex chromosome systems in fishes, as well as recent advances in our understanding of the evolutionary role of sex chromosome turnover in stickleback speciation.